Fungsi Komunikasi Keluarga dalam Pembentukan Kepribadian Remaja di Kelurahan Sikumana Kecamatan Maulafa Kota Kupang - Lony Novitha Kadja Rihi; Yeremia Djefri Manafe; Ferly Tanggu Hana (Universitas Nusa Cendana, 2018)
Communication is a process of delivering information (messages, ideas) from one party to another. The form of communication activities used are to write, read, speak and listen to others speak. The purpose of this thesis is to know the function of family communication in the formation of teen personality in Sikumana Village, Maulafa District, Kupang City. This research was conducted in Sikumana Village, RT 014 / RW 006 by taking the object of family communication function in the formation of teen personality. This study examines the function of family communication in the formation of teen personality. This research type is descriptive qualitative, that is studying data obtained in field by using data in the form of written or oral sentence, behavior, phenomenon, event of knowledge or object of study with emphasize on understanding, thinking and perception of researcher. The informants of this study are the people who are determined by purposive sampling, that is selected based on certain considerations that informants are considered competent in answering the questions of researchers. Primary data was obtained through interviews with resource persons at the time of the study. Secondary data is obtained through literature study in the form of books, journals and so on that related to the problem under study.The results obtained, showing the function of family communication in the formation of teen personality refers to the daily activities of the family. The function of family communication used in this research there are 2 functions, namely Social Function and Cultural Function. Apparently in Sikumana Village, RT 014 / RW 006, teenage personality is often complained of the unruly personality. This happens because the lack of attention from parents because of busy with work, family communication functions that do not work properly, teenagers who become disobedient to parents, lazy school, so that children listen to more peers and spend more time with friends, friend. The conclusions of this study indicate that the family communication function that occurs in Kelurahan Sikumana using Social Functions and Cultural Functions in shaping teen personality and expectations of parents so that their teenagers can become a better person without damaging their future.